2007
DOI: 10.1143/jjap.46.4613
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Image Evaluation of Welded Zone of Steel Plate using Photoacoustic Microscope

Abstract: The nondestructive evaluation (NDE) of welded steel plates was performed using photoacoustic microscope (PAM). Specimens were prepared by changing the maximum welding current to 5, 6.5, and 8 kA. A noncontact inspection without having to assemble a transducer was performed, and the results were compared with those of destructive inspection using an optical microscope. The agreement of NDE using a PAM and results from an actual shear fracture destructive test was good. The large fluctuation in the PA signal mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…[1][2][3][4][5][6] Above all, methods of visualization in real time are demanded. Results of these visualization contribute to nondestructive tests [7][8][9][10][11] and medical fields 12,13) as shown in the acoustical focusing lens, among others.…”
Section: Introductionmentioning
confidence: 89%
“…[1][2][3][4][5][6] Above all, methods of visualization in real time are demanded. Results of these visualization contribute to nondestructive tests [7][8][9][10][11] and medical fields 12,13) as shown in the acoustical focusing lens, among others.…”
Section: Introductionmentioning
confidence: 89%
“…The photoacoustic microscope (PAM) is a useful tool for non-destructive imaging [1][2][3] and quantitative measurements [4] of surface defects in solid specimens. Previously, the use of a line-focus laser beam for inspecting welded metal plates by photoacoustic (PA) imaging was proposed [5].…”
Section: Introductionmentioning
confidence: 99%
“…4,5) Photothermal and related techniques have been applied to the nondestructive investigation of solid materials. [6][7][8][9][10][11][12] Tokeshi et al reported a detection limit of 0.4 molecules in a 7-fL detection volume, as determined using a thermal lens microscope. 13) However, generally the sensitivity of PTL is inferior to LIF.…”
Section: Introductionmentioning
confidence: 99%